Ageism, moral sensitivity and nursing students' intentions to work with older people – A cross-sectional study. (June 2022) - Gherman, Mihaela-Alexandra; Arhiri, Laura; Holman, Andrei Corneliu
Abstract: Background: Nursing students' intentions to work with older people are low, despite a worldwide need for gerontological nursing, with ageism being the main culprit. Romania lacks legislation to prevent and combat elder abuse in healthcare, although it is alleged to be rampant among nursing staff. There is also a lack of research on nursing students' ageism toward older people and intentions to work with them. Objectives: Since ageism conflicts with nursing ethics, we expect moral sensitivity to lower ageism and increase intention to work with older people, while also moderating other socio-psychological influences. Because ageism and intention to work with older people are largely predicted by the same variables, we hypothesize that ageism may function as a mediator. Finally, we explore ageism among Romanian nursing students and its predictors in a culturally sensitive manner. Design: This is a cross-sectional, descriptive survey study. Settings: The study was conducted in Romania. Participants and methods: 408 nursing students completed online-administered questionnaires measuring intention to work with older people, ageism, moral sensitivity, death and ageing anxiety, knowledge of ageing, attitudes toward own ageing and intergenerational contact. Data were analyzed with Pearson's correlations, regressions with simple slope analyses and bootstrapped mediation analyses. Results: Ageism mediated the relationships between students' intentions to work with older people and knowledge of ageing, ageing anxiety, intergenerational contact quality, attitudes toward own ageing and moral sensitivity. Moral sensitivity decreased ageism and increased intention, while moderating the influence of contact quality, death and ageing anxiety, attitudes toward own ageing and knowledge of ageing on ageism. Additionally, it moderated the influence of perceived behavioral control on intention. Conclusions: Integrating moral sensitivity training in the nursing curricula could both decrease ageism in nursing students and increase their intention to work with older people, providing an efficient and low-cost strategy to aid students consider gerontological nursing for career advancement. Highlights: Moral sensitivity buffers socio-psychological ageist influences in nursing students. Moral sensitivity decreases ageism and increases intention to work in geriatrics. Ageism is a proximal predictor of intention, operating as a mediator. Knowledge of ageing and support to work in geriatrics should be provided. Moral sensitivity training should be included in nursing education curricula.